Geochemical Characteristics of Sunda Volcanic Arc in Sumatra and Andaman - Kurnio, Hananto (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.1.1-16Geochemical characteristics of Sunda volcanic belt are recognized from each characteristic of Weh Island, Tabuan Island in Semangko Bay, South Sumatra, and Andaman Islands. Trace and rare earth elements (REE) are produced by fumaroles in a marine environment of submarine volcano of Weh Island characterized by barium (Ba) as an indicator of sea water influence in the mineralization process, while sulphide minerals do not occur in this area. REE pattern compared to Mid Oceanic Ridge Basalt (MORB) shows a characteristic of subduction tectonics and is distributed in shallow coastal water of high energy. Based on comparison of REE contents in all samples, it reveals that volcanism process causes REE enrichments either in the past or in recent. Geochemical characteristics of Tabuan Island in Semangko Bay reveal the occurrence of hydrothermal mineralization followed by pervasive occurrences of sulphide minerals in vein-type disseminations enriched in Au, Ag, Zn, Pb, Cu, As, Sb, Ba, and Mn. Geochemical characteristics of Andaman Islands reveal imprint of substantial subduction component in the form of sediment fluid and melt and fluid-induced subduction component derived from altered oceanic crust.